Antibiotic Resistance and Integron of Vibrio cholerae Detection from School Street Foods in Jakarta - NADIA DEASHINTA; DIANA ELIZABETH WATURANGI; YOGIARA YOGIARA (Bogor Agricultural University, Indonesia, 2007)
Street foods represent foods and beverages prepared by vendors in streets or other public places, i.e. schools. Food safety issues perceive street foods as a potential major public risk. Street foods contaminated with toxigenic Vibrio cholerae may lead to serious poisoning to school-age children. In this study, 17 isolates of V. cholerae were obtained from nine (45%) of total 20 street foods samples collected in Jakarta. Five (29%) were confirmed to be V. cholerae O1, serotype Ogawa using biochemical tests and serological identification. Of the 17 V. cholerae isolates 47% proved to be resistant to ampicillin, 35% to trimethoprim, 17.6% to tetracycline, and 17.6% to streptomycin. A class 1 integrons bearing streptomycin/spectinomycin resistant gene cassette of aadA1c were discovered on isolate Vc25n. This may leads to horizontal transfer of the antibiotic resistant genes to other bacteria. Key words: foods, Vibrio cholerae, antibiotic resistance, integron